Phytosomes: A Novel Drug Delivery for Herbal Extracts - Bhise, Jayashri J.; Bhusnure, Omprakash G.; Jagtap, Sneha R.; Gholve, Sachin B.; Wale, Richa R. (Journal of Drug Delivery and Therapeutics, 2019)
The term “phyto” means plant while “some” means cell-like. Phytosome is novel emerging technique applied to phyto-pharmaceutical which contains phytoconstituents to herbal extract surrounds and bound by lipids. Phytosome shows better absorption, hence produces better bioavailability than the conventional herbal extracts. Because of their improved pharmacological and pharmacokinetic properties. Phytosomes are herbal formulation which has enhanced the therapeutic effects of the plant extracts and herbal lead molecule by increasing bioavailability in the target site compared to conventional herbal extracts. This is improved forms of herbal formulation which contain the bioactive phytoconstituents of herb essence enclosed and bound by a lipid. Phytosomes demonstrated improved pharmacokinetic and pharmacodynamic response than customary botanical extracts. Keywords: Phytosomes; Bioavailability, Phospolipids, phytoconstituents.